2016
DOI: 10.1051/matecconf/20163901010
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Enhanced Atomic Layer Deposition (PEALD) of TiN using the Organic Precursor Tetrakis(ethylmethylamido)Titanium (TEMAT)

Abstract: Abstract. This paper presents the plasma-enhanced atomic layer deposition (PEALD) of titanium nitride (TiN) using the organic precursor tetrakis(ethylmethylamido)titanium (TEMAT), with remote ammonia (NH3) plasma as reactant gas. This work investigates the impact of substrate temperature, from 150-350 C, and plasma times, from 5-30s, on deposition rate, resistivity, carbon content, N/Ti ratio and film density. The lowest resistivity of ~ 250 µΩ .cm was achieved at substrate temperatures 300-350 C and plasma ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The nitrogen precursors for the ALD of metal nitrides include NH 3 [212,275], hydrazine [276], N 2 plasma [277,278], and NH 3 plasma [261,262]. NH 3 is commonly used, given that the metal precursors are sufficiently reactive [212,275].…”
Section: Ald Precursors For Non-metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nitrogen precursors for the ALD of metal nitrides include NH 3 [212,275], hydrazine [276], N 2 plasma [277,278], and NH 3 plasma [261,262]. NH 3 is commonly used, given that the metal precursors are sufficiently reactive [212,275].…”
Section: Ald Precursors For Non-metalsmentioning
confidence: 99%
“…Using Ti(NEt 2 ) 4 and NH 3 plasma, TiN films with a low resistivity of ca. 250 µΩ cm were deposited at 300 • C; however, higher carbon concentration was observed at lower deposition temperatures [261]. Ta(NMe 2 ) 5 was used with H 2 plasma to deposit TaN [201].…”
Section: Metal Amidesmentioning
confidence: 99%
“…Few studies are dedicated to alkoxides (e. g. titanium tetraisopropoxide, TTIP 13 ), because such oxygen containing ligands should be avoided to prevent oxygen contamination. Most of the literature focus on alkylamides such as tetrakis(dimethylamino)titanium (TDMAT), tetrakis(diethylamino)titanium (TDEAT), tetrakis(ethylmethylamino)titanium (TEMAT) or heteroleptic molecules such as biscyclopentadienyl titanium triisopropylguanidinate (Cp 2 Ti[(N i Pr) 2 CN(H) i Pr]) [14][15][16][17][18][19] . Among those organometallic precursors, TDMAT is currently the most used and investigated in research laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Using TDEAT, Wang et al reported lowering the resistivity of halogen-free ALD TiN to 450 μΩ cm in an 18.1 nm film. Besides thermal ALD, PEALD was also applied to synthesize TiN using TDMAT and TEMATi as precursors.…”
Section: Introductionmentioning
confidence: 99%